STRATEGI PEMBANGUNAN KAWASAN PERBATASAN KALIMANTAN BARAT – SARAWAK DALAM KONTEKS PENGUATAN KETAHANAN NASIONAL - Marcus Lukman (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
The border of Indonesia and neighbouring state region ever peep out very complex strategic issues of economic life, political, social, cultural, law enforcement, defence and security state. It’s free Island of Simpadan and Ligitan to hand of Malaysia and Ambalat conflict are represent the real example of small part of the strategic issue becoming threat factual to sovereignty of Indonesia state. Special particularly in region border of West Kalimantan and Sarawak (East Malaysia) which is very loaded with the left behind problem, poorness and various tranasional crime. In consequence needed a correct development strategy to its eliminate so that created a strong national resilience in that area.